The Implementation of Inheritance Dispute Arrangement Based on Local Wisdom in Gayasan A, Jenggawah, Jember Regency - Erfina Fuadatul Khilmi; Arvina Hafidzah; Praptika Septi Femilia (Indonesian Academy of Social and Religious Research (IASRR), 2021)
Differences in understanding the distribution pattern of inheritance rights potentially cause disputes which fade the family relationships and merge endless conflicts among the family members. The aim of the research is to comprehend the implementation of inheritance dispute arrangement based on local wisdom as an alternative method in achieving the community’s balance and harmony that they still consider the arrangement through a court action as a taboo of settlement. The research shows several findings; factors that influence the differences in the distribution of inheritance in Gayasan A, Jenggawah, Jember Regency are the absence of communication between the heirs (the giver) and heirs, which is known as debik kek lopaen; and the community’s view of the heirs also influence the distribution of inheritance rights, so that local wisdom is needed as a strategic tool in arranging the disputes by implementing internal discussions among the family members mediated by a customary head and a sanction of exclusion (not diajepi). Data collection was conducted through a combination of literature study and field study by triangulating the results of observations, interviews and questionnaires. The research design applied was the sociology of law with an approach of problem on the unwritten customary law implemented in the community of Gayasan A as a social fact developed from the value system of the community and supported by a theoretical approach